Pemanfaatan Minyak Jelantah menjadi Lilin Aromaterapi pada Siswa Kelas X SMKN 10 Merangin - Zuhri, Rozana; Marlina, Leni; Wulandari, Eko; Yulianti, Eni; Andriyanto, Andriyanto (LPPM Universitas Bumigora, 2023)
Cooking oil that has been used will become used oil or used cooking oil. If this used cooking oil is reused continuously, it will have a negative impact on the health of the body and if it is disposed of carelessly it will pollute the environment. Used cooking oil needs to be minimized through recycle or reduce. Environmental pollution caused by used cooking oil has become an environmental problem with a wide impact. One solution to overcome this problem is to process used cooking oil as an alternative material for making aromatherapy candles. The type of community service applied is in the form of training. Methods The activities carried out using experimental methods and direct practice on how to make aromatherapy candles using used cooking oil. From the results of this community service activity, it was concluded that the increased knowledge of class X students of SMKN 10 Merangin regarding the impact of the use and disposal of used cooking oil on the environment and increased student skills regarding the manufacture of recycled products from used cooking oil in the form of aromatherapy candles.